An updated key to the species of Fannia Robineau-Desvoidy (Diptera: Fanniidae) of Southern South America, and the description of a new species from Mendoza, Argentina - Domínguez, M. Cecilia; Aballay, Fernando H. (Zootaxa, 2014)
The aim of this study is to describe Fannia puxcu sp. n., a new species of the genus Fannia Robineau-Desvoidy (Diptera: Fanniidae) that was collected in the Villavicencio Provincial Reserve in Mendoza, Argentina, and to present an updated key to the 27 species of Fannia Robineau-Desvoidy (Diptera: Fanniidae) of Southern South America. The male of F. puxcu sp. n. is described, and illustrations provided as well as distributional records and a discussion of its possible phylogenetic affinities.